BONA FIDES IN ROMAN CIVIL PROCEDURE - Rakočević, Milka (Ius Romanum, Periodicum Digitale, 2021)
Although not always distinguished as an explicit procedural phenomenon, abusus iuris doctrine has a long history and is familiar to all periods of historical development of civil procedure. As one of the basic principles of contemporary civil procedure, if analysed historically, it can be noted that the prohibition of abuse of procedural rights is neither modern nor contemporary in the legal meaning of those terms, nor in the historical retrospective loses the importance that characterize it in the modern civil procedure. Within the paper, the focus is set on the administration of justice in ancient Rome with particular interest on the institute of abuse of procedural rights. The paper discusses the beginnings and development of organized methods of legal protection in Roman civil procedure with the aim to determine its basic characteristic through different stages of its development and to analyse the frivolous behaviour of the parties before the tribunal and procedural mechanisms for supressing vexatious litigation. The historical retrospective is covering different periods of development of the Roman litigation. The main drive for analysis of the historical dimension of civil procedure in ancient Rome is to analyse the genesis and evolution of the principle of bona fides in Roman civil procedure
Keywords: roman civil procedure, abuse of procedural rights, vexatious litigation